2016
DOI: 10.1109/jlt.2016.2628438
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Modelling of a Six-Hole MOF

Abstract: Abstract-We model the drawing of a six-hole microstructured optical fibre with a combination of asymptotic techniques and a new efficient numerical method, and compare this to a previous set of experiments and finite element simulations. The new approach accurately models the deformation of the inner channels and predicts cross-sectional fibre geometries which are a better match to the experiments than the previous, more computationally expensive simulation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…For a radial length scale that is much smaller than the axial length scale, as assumed by Klupsch & Pan, the asymptotic fibre-drawing model of Stokes et al (2014Stokes et al ( , 2019) may be used for capillary collapse and yields analytic formulae relating the extent of collapse to the harmonic mean of the viscosity and the surface tension of the glass. The accuracy of this model is excellent for drawing of fibre from very slender preforms (Chen et al 2016b) and is expected to be excellent for capillary collapse which does not see the high draw ratios and sharp tapers seen in fibre drawing and which are known to cause discrepancies between models and experiments, especially when the radius of the preform is not sufficiently small relative to the neck-down length (Chen et al 2016a).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…For a radial length scale that is much smaller than the axial length scale, as assumed by Klupsch & Pan, the asymptotic fibre-drawing model of Stokes et al (2014Stokes et al ( , 2019) may be used for capillary collapse and yields analytic formulae relating the extent of collapse to the harmonic mean of the viscosity and the surface tension of the glass. The accuracy of this model is excellent for drawing of fibre from very slender preforms (Chen et al 2016b) and is expected to be excellent for capillary collapse which does not see the high draw ratios and sharp tapers seen in fibre drawing and which are known to cause discrepancies between models and experiments, especially when the radius of the preform is not sufficiently small relative to the neck-down length (Chen et al 2016a).…”
Section: Introductionmentioning
confidence: 95%
“…2015 a , b ; Chen et al. 2016 b ; Stokes, Wylie & Chen 2019), and the drawing of slender axisymmetric tubes is a particular case. Thus, 2-D models exist which are applicable to capillary collapse and which predate that of Klupsch & Pan (2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The asymptotic techniques applied in studies of this type have been shown to be accurate by Chen et al. (2016). All of these studies were focused on the steady states and did not consider the stability problem for the drawing of non-axisymmetric threads.…”
Section: Introductionmentioning
confidence: 99%